6x-2=4x-(-2x+2)

Simple and best practice solution for 6x-2=4x-(-2x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2=4x-(-2x+2) equation:


Simplifying
6x + -2 = 4x + -1(-2x + 2)

Reorder the terms:
-2 + 6x = 4x + -1(-2x + 2)

Reorder the terms:
-2 + 6x = 4x + -1(2 + -2x)
-2 + 6x = 4x + (2 * -1 + -2x * -1)
-2 + 6x = 4x + (-2 + 2x)

Reorder the terms:
-2 + 6x = -2 + 4x + 2x

Combine like terms: 4x + 2x = 6x
-2 + 6x = -2 + 6x

Add '2' to each side of the equation.
-2 + 2 + 6x = -2 + 2 + 6x

Combine like terms: -2 + 2 = 0
0 + 6x = -2 + 2 + 6x
6x = -2 + 2 + 6x

Combine like terms: -2 + 2 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| J=9(3.14)p | | 3x-3=2x-16 | | -5n-n=10 | | 3x-2=16-x^2 | | 185-u=252 | | 3x+5+6x=15 | | 14x+7-2=7 | | 11(y-2)=13(y+4) | | 3p^2+4p=8 | | 11T=8D+12pm | | 4(x+2)+3(2x-5)=31 | | (4x-25)+(3x-75)=180 | | 3-k=14 | | 6(4)+-25=7+-2(4) | | (8x+25)+(3x+75)=180 | | (2x-7)-(x-6)=14 | | 3x-3-24=4x-4 | | 2x-11=3x-7 | | y=16x+16+19 | | 1x-9=-27 | | 2+2=m | | 4x+7-7x=14 | | 2x+8=x-20 | | 9(y+3)=12(y+5) | | -6=7+x | | 12x^2-12x^3= | | 1.5y-0.2y= | | 9x-14+3(x-8)=7 | | 27-11p-13p=-9 | | 12+11y=-18-4y | | u-9=-5 | | 5-(-4)=3(n+2) |

Equations solver categories